Implementation of block artificial cooling units for gas preparation - Rubel, Victoriia; Maslenko, Maksym (Technology audit and production reserves, 2024)
The object of research is the process of implementation and use of block artificial cooling units in the technology of natural gas preparation. The research has confirmed the high efficiency of using artificial cooling units. Due to deep gas cooling, it is possible to achieve a significant increase in condensate production and improve gas quality. In addition, modern units are characterized by high energy efficiency and compactness. A comprehensive analysis of existing gas preparation technologies and a comparative assessment using block artificial cooling units revealed a number of significant advantages of the proposed system, namely: – block units provide deeper removal of heavy hydrocarbons, water and other impurities, which improves the quality of the final product; – due to lower gas temperature, more intensive condensation of heavy hydrocarbons is achieved, which leads to additional extraction of valuable components; – modern block units are equipped with energy-efficient equipment, which reduces energy costs; – the units have a modular design, which facilitates their transportation, unit and maintenance; – the use of block units allows to reduce emissions of harmful substances into the atmosphere; – the ability to adapt to different operating conditions and product quality requirements. The study found that existing natural gas preparation technologies have a number of disadvantages, such as: – low efficiency of gas purification; – high energy consumption; – complexity of maintenance; – large dimensions of the equipment. Despite some drawbacks, the introduction of block artificial cooling units is a promising direction for the development of the gas industry. The results of the study indicate the high efficiency of this technology and its economic feasibility in the long term.